2002
DOI: 10.1111/j.0014-3820.2002.tb01394.x
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Wing Color in Colias Butterflies: Heritability, Sex Linkage, and Population Divergence

Abstract: We investigated the genetic background of intraspecific variation in wing color across an elevational gradient in the butterfly Colias philodice eriphyle. The degree of wing melanization was an accelerating function of elevation, and differences in wing melanization persisted in a common environment. Full‐sibling analysis and parent‐offspring regression yielded consistent, moderate to high heritabilities for the degree of wing melanization. The breeding experiments also demonstrated that wing melanization is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 42 publications
4
76
3
Order By: Relevance
“…It is difficult to interpret such results; there seems to be no influence of sex chromosomes, because both sexes exhibit almost equal values for heritability, independently of the sex of the parent. Sex linked inheritance was reported by Ellers and Boggs (2002) for wing melanization in Colias. A sort of maternal effect could be suggested, since the values for h 2 are very low only when the mother's score is used (range 0.08-0.12); we cannot even reject the possibility of an epigenetic effect due to DNA methylation (this is currently under investigation by our group).…”
Section: Discussionmentioning
confidence: 97%
“…It is difficult to interpret such results; there seems to be no influence of sex chromosomes, because both sexes exhibit almost equal values for heritability, independently of the sex of the parent. Sex linked inheritance was reported by Ellers and Boggs (2002) for wing melanization in Colias. A sort of maternal effect could be suggested, since the values for h 2 are very low only when the mother's score is used (range 0.08-0.12); we cannot even reject the possibility of an epigenetic effect due to DNA methylation (this is currently under investigation by our group).…”
Section: Discussionmentioning
confidence: 97%
“…We used estimates of the phenotypic standard deviation of α for C. eriphyle (0.062) reported by Kingsolver (1983a) for population samples taken in 1980. Ellers and Boggs (2002) used parent–offspring breeding experiments to estimate the narrow‐sense heritability h 2 of wing melanin for C. eriphyle , yielding h 2  = 0.43 for males and 0.36 for females (Ellers & Boggs, 2002); we used a h 2 value of 0.40 for α 20 in our simulations. We used data for full‐sib families of C. eriphyle from a midelevation population (2.3 km) to estimate the phenotypic standard deviation of B as 0.083 (Higgins, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…For example, several authors have found significant family-level effects (i.e. family origin) on measures of larval and adult melanism when rearing progenies of wild-captured butterflies in a common garden experiment (Ellers and Boggs, 2002;Hazel, 2002;Davis et al, 2005). However, in most of these studies, potential maternal effects could not always be accounted for.…”
Section: Morphological and Molecular Mechanisms Of Melanismmentioning
confidence: 99%